Hawaii, Cannes, and Los Angeles : projecting South Korean cinema to the world - Lee, Sangjoon (2018)
In summer 2015, Star Wars: The Force Awakens dominated the box office in virtually every major film market on the planet. There were, however, two notable exceptions. Patrick Brezeski (The Hollywood Reporter) points out two markets where the force was not strong enough to hold local audiences – Vietnam and South Korea. At the South Korea box office, CJ Entertainment’s mountaineering adventure drama The Himalayas (Himallaya, 2015) outperformed The Force Awakens. Vietnam’s Star Wars-beating movie was, interestingly enough, Sweet 20 (Em là bà nội của anh), a remake of 2014 South Korean hit Miss Granny (Susanghan Kŭnyŏ). It was indeed a second regional remake. The Chinese version came first, only ten months earlier, with the title of 20 Once Again (Chóng fǎn èrshí suì, 2015). Surprisingly, all three versions were also produced (or co-produced) by CJ Entertainment, South Korea’s media giant. Brezeski, thus, concluded his article with this line: “If there’s any force to rival The Force, it might be just be the so-called “Hallyu, or Korean pop culture wave, which continues to dictate trends across much of Asia.